Perancangan Alat Pengering Mie Ramah Lingkungan - Setyanto, Nasir W.; Himawan, R.; D., Zefry; Arifianto, Endra Y.; M.S., Puteri Rina; N., Kurnia (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Noodle is a food product which is made from wheat, with or without additional ingredients. The products of noodle are generally used as the source of energy because the contents of carbohydrates are relatively high.Drainage is a process to extract or separate the water in the relatively small ammount from the substances using thermal energy. The purposes from this drainage process are: to decrease the water level from the subtances to have longer shelflife, decrease the subtances’ volume to ease and save the transport costs, packaging and storage.The main principple of drainage is extraction of the water from subtances as the result on process of heat transfer which is correlated with the difference of temperature between product’s suface with water’s surface in several location inside the products.Noodle drainage methods can be distinguished as Home Industrial Scale and Big Industrial Scale. Home Industrial Scale can be distinguished as Sun dry and Toaster. Big Industrial Scale can be distinguished as Toaster and Hot Dryer.In this research, noodle drying process are using the tools that can lessen the weaknesses which is owned by the previous tools used, including in big industry. The tool used in this research is using centrifugal force for drainage and blower with the low costs.Materials used in this research have a simple design thatmake it easy to be applied. Moreover the materials used are save for the food processing.Keywords: noodle, drainage, noodle drainage methods.